QOL-11. COMMUNICATION IN THE CONTEXT OF GLIOBLASTOMA TREATMENT: WHAT MATTERS MOST. (14th November 2022) - Boele, Florien; Butler, Sean; Nicklin, Emma; Pointon, Lucy; Short, Susan; Murray, Louise
Abstract: BACKGROUND: Given the poor prognosis of glioblastoma, it is critical that the benefits and burdens of treatments are clearly discussed with patients and family caregivers. We investigated experiences and preferences around glioblastoma treatment communication in patients, caregivers, and healthcare professionals (HCPs). METHODS: Semi-structured qualitative interviews were conducted with adult glioblastoma patients, their caregivers, and HCPs. Purposive sampling was used to capture views across the entire disease trajectory and different specialties. Interviews were recorded, transcribed verbatim, and analysed thematically. RESULTS: In total, 15 patients, 13 caregivers (in N =12 individual and N =8 dyadic interviews), and five HCPs participated ( N =5 individual interviews). Four main themes were identified. 1) Communication practice and preferences . Risks and side-effects of anti-tumour treatments were explained clearly, with information layered and revisited frequently to aid understanding. Treatment was often understood to be 'the only option', particularly at recurrence. Understanding the impact of side-effects on daily life could be enhanced, including those from supportive medication (e.g., corticosteroids); alongside more proactive communication about support services. 2) What matters most . Patients/caregivers valued being well-supported by a trusted treatment team, feeling involved, having a sense of control, and quality of life. HCPs similarly highlighted trust, maintaining independence and quality of life, and emotional support as key. 3) Decision-making . With limited treatment options, trust and control are crucial in decision-making among patients, caregivers, and HCPs. While patients ultimately prefer to follow HCP advice they want to be involved, consider all alternatives, and voice what matters to them. 4) Impact of Covid-19. During the pandemic, greater efforts to maintain good communication were necessary. While negative impacts of Covid-19 were limited, caregivers appeared most disadvantaged by pandemic-related restrictions (e.g., limited visiting). DISCUSSION: In glioblastoma treatment communication, building trusting relationships, maintaining a sense of control, and good support are identified by patients, caregivers, and HCPs as critical.